Sweet taste signaling functions as a hypothalamic glucose sensor - Ren, Xueying; Zhou, Ligang; Terwilliger, Rose; Newton, Samuel; De Araujo, Ivan E. (Frontiers in Integrative Neuroscience, 2009)
Brain glucosensing is essential for normal body glucose homeostasis and neuronal function. However, the exact signaling mechanisms involved in the neuronal sensing of extracellular glucose levels remain poorly understood. Of particular interest is the identification of candidate membrane molecular sensors allowing neurons to change firing rates independently of intracellular glucose metabolism. Here we describe for the first time the expression of the taste receptor genes Tas1r1, Tas1r2 and Tas1r3, and their associated G-protein genes, in the mammalian brain. Neuronal expression of taste genes was detected in different nutrient-sensing forebrain regions, including the paraventricular and arcuate nuclei of the hypothalamus, the CA fields and dentate gyrus of the hippocampus, the habenula, and cortex. Expression was also observed in the intra-ventricular epithelial cells of the choroid plexus. These same regions were found to express the corresponding gene products that form the heterodimeric T1R2/T1R3 and T1R1/T1R3 sweet and L-amino acid taste G-protein coupled receptors, respectively. These regions were also found to express the taste G-protein α-Gustducin. Moreover, in vivo studies in mice demonstrate that the hypothalamic expression of taste-related genes is regulated by the nutritional state of the animal, with food deprivation significantly increasing expression levels of Tas1r1 and Tas1r2 in hypothalamus, but not in cortex. Furthermore, exposing mouse hypothalamic cells to a low-glucose medium, while maintaining normal L-amino acid concentrations, specifically resulted in higher expression levels of the sweet-associated gene Tas1r2. This latter effect was reversed by adding the non-metabolizable artificial sweetener sucralose to the low-glucose medium, indicating that taste-like signaling in hypothalamic neurons does not require intracellular glucose oxidation. Our findings suggest that the G-protein coupled sweet receptor T1R2/T1R3 is a brain glucosensor.